2020
DOI: 10.1007/s42452-020-1996-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of load distribution on longitudinal and lateral forces acting on each wheel of a compact electric vehicle

Abstract: Autonomous vehicle is gaining popularity in the market worldwide. Most autonomous vehicle are based on electric vehicles since they are easy to control. The torque control of electric vehicles is precise and easy since electric motor torque can be manipulated by controlling the motor current. Furthermore, the load of the vehicle affects the motor torque of an electric vehicle. A higher vehicle load requires high motor torque to propel the vehicle. Often in autonomous vehicle, the vehicle parameters and stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In [90], a simulation model of a two rear in-wheel motors is used to analyze the effect of vehicle load on longitudinal and lateral forces. It is observed that an additional load added on the side of the direction of lateral motion increases the lateral force generated and causes the tires to approach the tire friction circle limit, thereby reduceing EV performance.…”
Section: Safety and Riskmentioning
confidence: 99%
“…In [90], a simulation model of a two rear in-wheel motors is used to analyze the effect of vehicle load on longitudinal and lateral forces. It is observed that an additional load added on the side of the direction of lateral motion increases the lateral force generated and causes the tires to approach the tire friction circle limit, thereby reduceing EV performance.…”
Section: Safety and Riskmentioning
confidence: 99%
“…Moreover, the increased height adds a significant lateral force increase and the resulting rolling moment to the other associated issues such as forces on the surface [7]. Even different wind conditions are important factors in determining the risk of a train overturning and derailment [8].…”
Section: Introductionmentioning
confidence: 99%
“…The most active and passive safety control systems are developed using a vehicle dynamic model, requiring the longitudinal tire forces to determine vehicle parameters, including longitudinal acceleration, braking distance, and slip rate [7]. Moreover, according to linear and nonlinear vehicle dynamic models, the longitudinal force acting on the tire is a major factor affecting the behaviour of a vehicle [8]. Thus, the estimation of the longitudinal force of intelligent tire has a great impact on vehicle handling and safety.…”
Section: Introductionmentioning
confidence: 99%